Preconditioning Enhances the Therapeutic Effects of Mesenchymal Stem Cells on Colitis Through PGE2-Mediated T-Cell Modulation - Yang, Fu Yuan; Chen, Rui; Zhang, Xiaohu; Huang, Biao; Tsang, Lai Ling; Li, Xican; Jiang, Xiaohua (Cell transplantation, 2018)
Mesenchymal stem cell (MSC)-based cell therapy has been demonstrated as a promising strategy in the treatment of inflammatory bowel disease (IBD), which is considered an immune disease. While the exact mechanisms underlying the therapeutic effect of MSCs are still unclear, MSCs display anti-inflammatory and immunomodulatory effects by interacting with various immunoregulatory cells. Our previous studies have shown that MSCs can be preconditioned and deconditioned with enhanced cell survival, differentiation and migration. In this study, we evaluated the effect of preconditioning on the immunoregulatory function of human umbilical cord-derived MSCs (hUCMSCs) and their therapeutic effect on treating IBD. Our results show that intraperitoneal administration of deconditioned hUCMSCs (De-hUCMSCs) reduces the disease activity index (DAI), histological colitis score and destruction of the epithelial barrier, and increases the body weight recovery more intensively than that of un-manipulated hUCMSCs. In addition, De-hUCMSCs but not hUCMSCs elicit anti-apoptotic effects via induction of the ERK pathway during the early stage of IBD development. In vitro co-culture studies indicate that De-hUCMSCs suppress T-cell proliferation and activation more markedly than hUCMSCs. Moreover, De-hUCMSCs block the induction of inflammatory cytokines such as tumor necrosis factor (TNF)α and interleukin (IL)-2, while promoting the secretion of the anti-inflammatory cytokine IL-10 in T-cells. Mechanically, we find that prostaglandin E2 (PGE2) secretion is significantly increased in De-hUCMSCs, the suppression of which dramatically abrogates the inhibitory effect of De-hUCMSCs on T-cell activation, implying that the crosstalk between De-hUCMSCs and T-cells is mediated by PGE2. Together, we have demonstrated that preconditioning enhances the immunosuppressive and therapeutic effects of hUCMSCs on treating IBD via increased secretion of PGE2.